Associative processing using negative capacitance FDSOI transistor for pattern recognition. (October 2020) - Rajasekharan, Dinesh; Kushwaha, Pragya; Chauhan, Yogesh Singh
Abstract: A novel method for associative processing, using negative capacitance FDSOI (NC-FDSOI) transistors, is presented in this work. Distance computing cell (DCC), that is the basic building block of the associative processing system, is designed using only five transistors. For processing an input pattern, this NC-FDSOI DCC based associative processing system requires fewer transistors and consumes 150 to 500 times lower energy, in comparison with the conventional CMOS Boolean system. The functionality of the DCC is achieved in this small five transistor circuit because of the sharp switching of the ferroelectric polarization.